2016
DOI: 10.1007/s11356-016-6909-5
|View full text |Cite
|
Sign up to set email alerts
|

Sono assisted electrocoagulation process for the removal of pollutant from pulp and paper industry effluent

Abstract: In the present work, the efficiency of the sonication, electrocoagulation, and sono-electrocoagulation process for removal of pollutants from the industrial effluent of the pulp and paper industry was compared. The experimental results showed that the sono-electrocoagulation process yielded higher pollutant removal percentage compared to the sonication and electrocoagulation process alone. The effect of the operating parameters in the sono-electrocoagulation process such as electrolyte concentration (1-5 g/L),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…El-Ashtoukhy et al [47] observed a specific energy consumption of 15.1 kWh/kg for the treatment of car-wash effluents with COD concentrations between 350 and 550 mg/L at 115 A/m 2 and pH 7.15. Asaithambi et al [22] demonstrate that the lower the COD concentration, the higher the specific energy consumption, and the specific energy consumption value observed in this work is average compared to those commonly observed by other authors [13,17]. The electrocoagulation effluent in optimized conditions was completely characterized, according to Table 4.…”
Section: +supporting
confidence: 56%
See 2 more Smart Citations
“…El-Ashtoukhy et al [47] observed a specific energy consumption of 15.1 kWh/kg for the treatment of car-wash effluents with COD concentrations between 350 and 550 mg/L at 115 A/m 2 and pH 7.15. Asaithambi et al [22] demonstrate that the lower the COD concentration, the higher the specific energy consumption, and the specific energy consumption value observed in this work is average compared to those commonly observed by other authors [13,17]. The electrocoagulation effluent in optimized conditions was completely characterized, according to Table 4.…”
Section: +supporting
confidence: 56%
“…This therefore causes the potentiation of coagulation and the removal of contaminants. The greater current density also increases the coagulant surface area, due to the active sites and the H 2 bubble density generated at the cathode [22,45], implying the flotation of pollutants and greater removal of COD. Moreover, the increased current intensity results in a significant decrease in the diameter of the gas bubbles, which accelerates the efficiency of the electrocoagulation treatment [44].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…us, the intermittent ultrasonic technique was found to be compatible with sono-EC. Asaithambi et al [157] concluded that sonication, electrocoagulation, and sono-assisted electrocoagulation methods were successfully used to treat pulp and paper mill effluent and that the results were compared in terms of colour removal, COD removal, and energy consumption.…”
Section: Sono-electrocoagulationmentioning
confidence: 99%
“…[4][5][6] However, effluent from the biorenery industry, which makes quite a large proportion of industrial wastewater, has been particularly challenging to address because of its high total organic carbon (TOC) content, strong alkalinity and even toxicity. [7][8][9] Current disposal methods mainly include coagulation, precipitation, biological aeration or the introduction of oxidizing agents such as Fenton's reagent, ozone and peroxide. 10,11 By the method of oxygen delignication, 51, 57 and 43% of BOD 3 , COD and color were reduced of the sodaanthraquinone pulping effluent.…”
Section: Introductionmentioning
confidence: 99%